Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0143715
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regulatory CD4 T Cells in Maintaining Tolerance in a Mouse Model of Autoimmune Hepatitis

Abstract: BackgroundThe role of regulatory CD4 T cells (Treg) in immune-mediated liver disease is still under debate. It remains disputed whether Treg suppress T cell-mediated hepatitis in vivo and whether hepatic regulatory T cells are functional in patients with autoimmune hepatitis.MethodsWe used TF-OVA mice, which express ovalbumin in hepatocytes, to investigate the impact of Treg in a model of autoimmune hepatitis. Treg isolated from inflamed livers of TF-OVA mice were tested for their functionality in vitro. By em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…Several studies have suggested that impaired T reg function is responsible for over-activation of CD4 + and CD8 + T cells, which can lead to a breakdown in tolerance to liver antigens and a progression towards liver disease [36, 37]. Here, we showed that type II NKT cells may also play a role in the establishment of AIH.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have suggested that impaired T reg function is responsible for over-activation of CD4 + and CD8 + T cells, which can lead to a breakdown in tolerance to liver antigens and a progression towards liver disease [36, 37]. Here, we showed that type II NKT cells may also play a role in the establishment of AIH.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to effector T cells, Tregs are important regulators of immune tolerance and inflammation response. In this study, we found lower levels of Tregs in AIH patients and in EAH mice in a time-dependent manner, which were consistent with previous studies [ 18 , 32 , 33 ] but were different from another report [ 19 ]. Conflicting results may be due to differences in methodology, or detection markers of the definition of Tregs, because Moritz et al considered CD4 + CD25 high CD127 low FoxP3 + T cells as Tregs in their study.…”
Section: Discussionsupporting
confidence: 84%
“…CD4 1 T cell fate and effector functions are dictated by integration of environmental cues and costimulatory properties of APCs. The inflammatory and autoimmune manifestations (3,12,(30)(31)(32) of liver disease suggest that the physiologic microenvironment critically contributes to systemic tolerance; perturbations can have deleterious consequences. Alterations in the liver microenvironment during fibrosis can facilitate activation of typically hyporesponsive liver-resident APCs, resulting in enhanced T cell priming.…”
Section: Resultsmentioning
confidence: 99%
“…Although pretransplant indicators of graft acceptance rates are not well defined, there is evidence that immune responses within the liver may contribute to systemic tolerance of foreign antigens—including allografts . Moreover, perturbations within the liver microenvironment, such as chronic fibrosis, can manifest extrahepatically as inflammatory and autoimmune disorders, largely T cell–mediated phenomena . Here, we will review the influence of the liver microenvironment particularly on CD4 + T cell subset help and associated alterations during liver disease and how it can contribute to breaks in tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation